INTEGRASI MATERI PMR MULA PADA PEMBELAJARAN OLAHRAGA UNTUK MENUMBUHKAN KESADARAN TOLONG-MENOLONG SISWA MI - Nur Amrina Zulfa; Bahtiar Firdiansyah (MURABBI, 2026)
The high risk of injury in sports at Islamic Elementary Schools (MI) emphasizes the importance of safety-based learning and fostering mutual aid awareness among students. Initial observations indicate that only about 25% of students are aware of the need to help an injured friend. This study aims to examine the integration of First Aid (RMP) material into sports learning and identify supporting and inhibiting factors in its implementation, as well as analyze its contribution to mutual aid awareness among MI students. The approach used is descriptive qualitative with field research on fourth-grade students at MI Negeri Kudus, Central Java. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model. The results of the study indicate that integration is implemented systematically through lesson planning, direct practice, and role-playing simulations supported by complete health and safety facilities and high student enthusiasm. This integration successfully fosters four indicators of mutual aid awareness: preventive independence, altruistic responsiveness, technical action efficacy, and interactive collaboration. In conclusion, the integration of practical safety training into physical activities can transform moral understanding from theoretical to real, empathetic actions. This program can serve as a reference for building a caring and responsive culture from an early age while also strengthening the competency of PGMI students as future educators.